Penggunaan Paradigma Integrasi-Interkoneksi dalam Proses Pembelajaran di Program Pascasarjana UIN Sunan Kalijaga Yogyakarta - AHMAD IZUDIN (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2017)
This article analyzes the utilization of integrative and inter-connective con-cepts in the learning process of Islamic studies at the graduate program in State Islamic University of Sunan Kalijaga. This study explores the experiences of lec-turers and students at the interdisciplinary Islamic studies at the graduate pro-gram. Based on the interview and observation, the author highlights two types of learning processes. First, lecturer at UIN Sunan Kalijaga have inserted notions integrative and inter-connective concepts as well as Islamic values and interdisci-plinary approach in their syllabus and learning plan. Second, students have given various responses to the way lecturers teach in the class. According to students, lecturers graduated from western educational institutions, either Europe or America, stimulated students to think critically use interdisciplinary approach in resolving the problems. There are also some lecturers who use a normative ap-proach in conceiving the debates and critical thinking in Islamic studies.